Synthesis, Characterization, and DFT Computational Study of Cu(II) Complex with 3-Hydroxybenzoate - Fastabiqul Khoirot; Muhammad David Julian Syach; Sentot Budi Rahardjo; Triana Kusumaningsih (ALCHEMY Jurnal Penelitian Kimia, 2026)
This study focuses on the synthesis, characterization, and density functional theory (DFT) computational study of Cu(II) complexes with 3-hydroxybenzoic acid ligands. The synthesis process was carried out by reacting CuCl₂·2H₂O with 3-hydroxybenzoic acid ligands in methanol, refluxing for 3 hours, and allowing the mixture to stand until complex precipitation formed. The complex formula was determined by atomic absorption spectrometry (AAS), thermogravimetric analysis (TGA), and molar conductivity measurements (41 S·cm2·mol-1), indicating that Cl⁻ acts as a counterion and that the complex formula is [Cu(3-hydroxybenzoate)2]Cl2·4H2O. The complex exhibits a single electronic absorption peak at 914 nm, indicating ligand-metal charge transfer (LMCT) and d-d transitions, consistent with a distorted square-planar geometry. The infrared spectrum shows a phenolic –OH band, indicating that –OH is not deprotonated. Computational methods were used to reveal the electronic structure and molecular geometry, and to verify the experimental data. This complex forms a distorted square planar structure.